Dylematy rozwoju infrastruktury gospodarczej wsi i rolnictwa na przykładzie województwa poznańskiego - Wilczyńska, Kamila (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
The development of village infrastructure requires a number of steps connected with large capital investment. Usually, infrastructural investment does not bring spectacular quick direct effects. It takes more time to be carried out and its effects can be seen usually some time after the beginning of exploitation. A review of developmental processes of infrastructural equipment of villages and agriculture in Poznań Province between 1978 - 1987, i.e. in the period of considerable set-back in the economic growth of the country, shows that the civilization level of villages is still far from municipal standards. Besides, the principle of complementarity in investment undertakings is not observed. Despite economic difficulties, small-scale investment (e.g. investing in non-conventional sources of energy) is still neglected. In view of priority granted to food economy one can say that the development of economic infrastructure of villages and agriculture does not correspond with the needs of agriculture and food economy, limiting to a considerable extent their growth.
Dilemma of the development of economic infrastructure of villages and agriculture on the example of Poznań province